Exploring the moderating role of construal levels on the impact of process vs outcome attributes on service evaluations. Issue 3 (20th September 2019) - Tatavarthy, Aruna Divya; Chatterjee, Swagato; Sharma, Piyush
Abstract : Purpose: The purpose of this paper is to develop and test an integrated conceptual framework using construal level theory (CLT) to explain the differences in the effects of process and outcome service attributes on overall service evaluation and customer satisfaction based on consumption context (social), evaluation context (temporal) and individual characteristics (expertise). Design/methodology/approach: The authors use two lab experiments (hotel and restaurant settings) and a field study of online reviews posted by actual hotel customers to test all the hypotheses. Findings: Process (outcome) attributes have a stronger influence on service evaluations under low-level (high-level) construal. Specifically, process attributes have a stronger influence when customers are accompanied by proximal (vs distal) social group, evaluate a service under near (vs distant) temporal frame or have high (vs low) level of customer expertise. Practical implications: Service managers can use the findings about the differences in the influence of social, temporal and individual variables on customer evaluations under process and outcome attributes to improve customers' service experiences and satisfaction. Originality/value: This paper extends past research on the influence of construal levels on customer decision making by exploring the differences in the effects of process vs outcome service attributes on overall service evaluation and customer satisfaction, under the influence of low (vs high) construal levels triggered by social, temporal and individual variables.